A novel Linear Programming formulation of maximum lifetime routing problem in wireless sensor networks. (1st January 2013) - Kartal Çetin, Bilge; Prasad, Neeli Rashmi; Prasad, Ramjee
In wireless sensor networks, one of the key challenges is to achieve minimum energy consumption to maximise network lifetime. In fact, lifetime depends on many parameters: the topology of the sensor network, the data aggregation regime in the network, the channel access schemes, the routing protocols, and the energy model for transmission. In this paper, we tackle the routing challenge for maximum lifetime of the sensor network. We introduce a novel Linear Programming (LP) approach to the maximum lifetime routing problem. To the best of our knowledge, this is the first mathematical programming of the maximum lifetime routing problem that considers the operation modes of the node. Solution of the LP gives the upper analytical bound for the network lifetime. To illustrate the application of the optimisation model, we solved the problem for different parameter settings for an example network.